Le débat Samuelson-Lerner et les régimes de retraite publics - Ascah, Louis (L'Actualité économique)

(untitled) (HEC Montréal, 1978)
This article reviews the Samuelson-Lerner debate and its implications for the design of public pension plans. Pay-as-you-go public pension plans can provide a fictitious rate of interest equal to the rate of growth of the economy. The conclusion that pay-as-you-go financing provides greater welfare than a funded plan when the rate of growth is greater than the rate of return and vice-versa holds only in a steady state and pension policy should not be based on artificial worlds which can never exist.